The role of internal control in the relationship of board gender diversity, audit committee, and independent commissioner on tax aggressiveness - Nanik Sri Utaminingsih; Dini Kurniasih; Maylia Pramono Sari; Monica Rahardian Ary Helmina (Cogent Business & Management, 2022)
This study aims to obtain empirical evidence regarding the effect of gender diversity on the board of commissioners, audit committees, and independent commissioners on tax aggressiveness, as well as the role of internal control as a moderating variable. The population is property, real estate, and building construction companies listed on the Indonesia Stock Exchange for the 2015-2020 period. Sample selection using the purposive sampling technique obtained 23 companies with 138 units of analysis (panel data). The results show that the board's gender diversity has a significant negative effect on tax aggressiveness. The audit committee and independent commissioners have no effect on tax aggressiveness. Internal control is not able to moderate the relationship between them. This research is useful for the company's management to determine a strategy for carrying out tax aggressiveness. Further research combines internal and external factors of the company and uses other factors that can affect tax aggressiveness.
Keywords: 650; audit committee; board gender diversity; Tax aggressiveness; independent commissioner; internal control